STUDENTS’ NARRATIVE READING COMPREHENSION THROUGH STORY FACE - Karomah, Rifhatul; Siminto, Siminto; Qamariah, Zaitun (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2023)
The purpose of this research is to ascertain how the story face method affects students' reading comprehension of narrative texts. The study was carried out at MA Hidayatul Insan Palangka Raya's class X. One class was picked by the researcher to be the experimental class. Purposive sampling was the method utilized to gather research data by choosing 16 students and administering pre- and post-tests. The story face method was used by the experimental class to learn English. The paired sample t-test method was used to examine the data gathered for this investigation. According to the study's findings, adopting the story face method significantly improves students' reading comprehension of narrative texts. The data analysis reveals that the sig. (2-tailed) is 0.00<0.05, which means that H0 is rejected and H1 is accepted. As a consequence, there is an average difference between the pre-test and post-test scores, indicating that the story face method has an impact on how well students understand narrative texts.